Stress analysis of heavy duty truck chassis using finite element method - Kurdi, Ojo; Abd. Rahman, Roslan; Tamin, Mohd. Nasir (2008)
One of the most important steps in development of a new truck chassis is the prediction of fatigue life span and durability loading of the chassis frame. The age of many truck chassis in Malaysia are of more than 20 years and there is always a question arising whether the chassis is still safe to use. Thus, fatigue study and life prediction on the chassis is necessary in order to verify the safety of this chassis during its operation. Stress analysis using Finite Element Method (FEM) can be used to locate the critical point which has the highest stress. This critical point is one of the factors that may cause the fatigue failure. The magnitude of the stress can used to predict the life span of the truck chassis. In this study, the stress analysis is accomplished by the commercial finite element packaged ABAQUS.